Kaizen implementation in oil field project development process in PT. CPI - Adijaya, Ficky Kusuma (2014)
Drilling new wells is an important activity to arrest production decline in every oil company, no difference in PT.Cahaya Putera Indonesia (CPI). The project development process cycle time is critical to make sure the team can deliver the quantity of new wells proposals.Activities in the project development process need to be revisited and evaluated to deliver most value and eliminate non-adding value activities.During the value stream mapping approximately 50% of the activities are considered redundant thus is waste to the whole process.Much of the analysis can be done in a centralized manner and then used it to multiple projects instead of keep re-inventing the wheels in every project.Kaizen implementation have reduced phase 1-3 cycle time by 36%, 36% and 11 % respectively.In this research, Kaizen implementation was only to reduce cycle time for first three phases.It was not intended to improve decision quality of each project.Future analysis could add six sigma efforts to CPDEP to increase quality decision of projects.